The Remodulation of Actin Bundles during the Stimulation of Mitochondria in Adult Human Fibroblasts in Response to Light - Soňa Olejárová; Denis Horváth; Veronika Huntošová (MDPI AG, 2023)
β-actin belongs to cytoskeletal structures that change dynamically in cells according to various stimuli. Human skin can be considered as an organ that is very frequently exposed to various stress factors, of which light plays an important role. The present study focuses on adult human fibroblasts exposed to two types of light stress. Orange light with a wavelength of 590 nm was used here to stimulate the photosensitizer localized in the cells as a residual dose of photodynamic therapy (PDT). On the other hand, near-infrared light with a wavelength of 808 nm was considered for photobiomodulation (PBM), which is often used in healing processes. Confocal fluorescence microscopy was used to observe changes in intercellular communication, mitochondrial structures, and cytoskeletal dynamics defined by the remodulation of β-actin of fibroblasts. The number of β-actin bundles forming spherical structures was detected after light exposure. These structures as β-actin oligomers were confirmed with super-resolution microscopy. While PDT led to the disintegration of actin oligomers, PBM increased their number. The interaction of β-actin with mitochondria was observed. The combination of PDT and PBM treatments is important to minimize the side effects of cancer treatment with PDT on healthy cells, as shown by the cell metabolism assay in this work. In this work, β-actin is presented as an important parameter that changes and is involved in the response of cells to PDT and PBM.